The E-Learning Design for Problem Based Learning in Dynamic Fluid Topic using Microsoft Sway - Prihartini Khoirun Nissa; Benedikta Lorenza Dheanti (Universitas Negeri Jakarta, 2021)
The development of information and communication technology (ICT) based on education can be an opportunity to improve the learning process. Learning in the pandemic era Covid-19 needs media that help teachers and students enthusiasm for learning. The lessons with e-learning are flexible and easy to use. Microsoft Sway 365 is one of the e-learning that can be used because of the features such as presentation, text, images, video, and sound. This study aims to produce e-learning using Microsoft Sway on Dynamic Fluid. This study uses an R&D method with the 4D model but only defines, designs, and develops stages. Media experts and material experts validated the e-learning. The validity test result from content experts showed that the e-learning using sway was feasible with 77.7% and from media experts was feasible with 77.5%. The study concludes that e-learning with Microsoft Sway is flexible, easy to use, can support physics learning with fun, and feasible to be used as a teaching medium that helps students in explanatory activities.